The substantive right to environment and the procedural environmental rights under the Aarhus Convention – Part I - Jendrośka, Jerzy (The Opole Studies in Administration and Law, 2024)
The current article provides Part I of the article which aims at examining the mutual relations between substantive and procedural environmental rights against the background of the typology of the substantive rights to the environment and challenges encountered when designing the right to a healthy environment. Part I provides the background analysis in this respect. It presents the origins of the term “right to environment” and various approaches to its meaning, in particular differences between the “right to have access to natural environment” and the “right to a healthy environment”. This is followed by presenting two possible approaches to the meaning of the term “right to a healthy environment” and their consequences. On this basis the article shows the three main methods of addressing concerns regarding environmental quality within human rights system and the relation between anthropocentric and ecocentric approach. Following this, the article presents the main challenges encountered when creating “right to a healthy environment”, in particular the issue of fitting this right into the existing system of protecting human rights and limitations related to “greening” of other human rights. Finally the current article provides a short overview of the the development of the respective legal provisions regarding environmental rights, including both human rights and Rights of Nature. Part I is concluded with some comments regarding the trend towards developing procedural environmental rights and expectations towards the UNECE Aarhus Convention and its role in protecting substantive environmental rights and participatory democracy – which is the link to Part II which addresses these issues in detail and concludes that access to justice provisions under the Aarhus Convention neither provide sufficient means to protect environmental rights nor – in light of the various conceptual roots of the Convention - should be treated as having only such a role.